Fabrication And Characterization Of Eco-Friendly Denture Adhesive Filled With Starches For Dental Application - Hilmi, Bazli (2020)
Starch is widely used in various industrial applications due to its good adhesiveness and many other excellent properties. However, there are still some drawbacks of native starch in terms of mechanical strength, but the limitations can be overcome by modification techniques. Since there is limited involvement of starch in dental application and the current available denture adhesives are reported to have several limitations and shortcomings for example, lack of bonding strength to hold the denture, the starches are explored for its potential in denture adhesive. Hence, this research focuses on the development of new formulation of denture adhesives which is called as eco-friendly denture adhesives (EFDAs) by studying the effects of the addition of different types of native and modified starches as fillers in denture adhesive properties for dental applications. The properties such as tensile bonding strength (TBS), shear strength, adhesiveness, hardness, pH and solubility of fabricated EFDAs in comparison with a selected commercial denture adhesive (CDA) were investigated. The investigated starches were corn, potato, sago, tapioca and wheat. The EFDAs were prepared with 5, 10 and 15% of starch filler loading. The starches were modified via oxidation technique by using sodium hypochlorite (NaOCl) and hydrogen peroxide (H2O2). The characterization tests of starch powders such as particle size analysis (PSA), Fourier Transform Infrared (FTIR) spectroscopy and UltraViolet-visible (UV-vis) spectrometry were performed. The mechanical and physical tests such as TBS, shear strength, adhesiveness, hardness, pH test and solubility were conducted on the fabricated EFDAs. Furthermore, antimicrobial test by using agar well diffusion and broth dilution methods and cytotoxicity test by using an Alamar Blue (AB) and 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assays for biological analysis were conducted. Mechanical analysis indicated that produced EFDAs have higher TBS, shear strength, adhesiveness and hardness as compared to the CDA with the increase percentage up to 121.8%, 162.3%, 368.2% and 343.5%, respectively. The optimum properties were associated with wheat starch filler loading at 5% and followed by corn, sago, potato, and tapioca starches. The properties also decreased as the starch filler loading increased to 10% and 15%. The EFDAs incorporated with peppermint oil and tea tree oil were inhibiting the growth of C. albicans, S. aureus and E. coli microorganisms and the EFDA samples were also non-toxic to the periodontal ligament fibroblasts (PDLFs) up to day four. EFDA has good potential to be used as a natural based denture adhesive due to the promising properties especially EFDA with wheat starch modified by NaOCl at 5% filler loading because it shows the highest mechanical properties as well as non-toxic effect which are important in biological environment.